Kernel-based local order estimation of nonlinear nonparametric systems. (January 2015) - Zhao, Wenxiao; Chen, Han-Fu; Bai, Er-wei; Li, Kang
Abstract: We consider the local order estimation of nonlinear autoregressive systems with exogenous inputs (NARX), which may have different local dimensions at different points. By minimizing the kernel-based local information criterion introduced in this paper, the strongly consistent estimates for the local orders of the NARX system at points of interest are obtained. The modification of the criterion and a simple procedure of searching the minimum of the criterion, are also discussed. The theoretical results derived here are tested by simulation examples.